2006
DOI: 10.3354/meps325243
|View full text |Cite
|
Sign up to set email alerts
|

Prey switching of cod and whiting in the North Sea

Abstract: Predator-prey switching may stabilise predator-prey interactions, promote co-existence of prey that share a common predator, and increase the overall stability of homogeneous systems of interacting species. This study presents an investigation of prey switching of 2 major North Sea fish predators, cod Gadus morhua and whiting Merlangius merlangus. Relative food composition derived from analysis of more than 36 000 stomachs is compared to the relative density of fish prey reflected by trawl survey catches, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 57 publications
0
10
1
Order By: Relevance
“…However, in both systems, we observed clear evidence for negative switching, which is likely to have a destabilizing effect (Chesson 1984). Several empirical studies showed that negative switching may be observed in marine (Kean-Howie et al 1988, Rindorf et al 2006) and terrestrial ecosystems (Weale et al 2000, Palma et al 2006, Hellström et al 2014). Several empirical studies showed that negative switching may be observed in marine (Kean-Howie et al 1988, Rindorf et al 2006) and terrestrial ecosystems (Weale et al 2000, Palma et al 2006, Hellström et al 2014).…”
Section: The Occurrence Of Negative Switchingmentioning
confidence: 50%
“…However, in both systems, we observed clear evidence for negative switching, which is likely to have a destabilizing effect (Chesson 1984). Several empirical studies showed that negative switching may be observed in marine (Kean-Howie et al 1988, Rindorf et al 2006) and terrestrial ecosystems (Weale et al 2000, Palma et al 2006, Hellström et al 2014). Several empirical studies showed that negative switching may be observed in marine (Kean-Howie et al 1988, Rindorf et al 2006) and terrestrial ecosystems (Weale et al 2000, Palma et al 2006, Hellström et al 2014).…”
Section: The Occurrence Of Negative Switchingmentioning
confidence: 50%
“…When the exponent is larger than 1, the predator exhibits prey switching. When the exponent is smaller than 1, the predator is said to exhibit negative prey switching, because it consumes disproportionately less of the more available prey (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…Most piscivorous fish species are considered generalist predators, implying that they consume prey based on encounter rates. It is less clear how marine fish alter foraging tactics and locations based on the availability of prey, i.e., exhibit a true switching response (Rindorf et al 2006). Clearly, prey switching would dampen bottom-up effects of fishery-induced reduction in forage species.…”
Section: Discussionmentioning
confidence: 99%